HUBUNGAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DAN KEMAMPUAN MENYELESAIKAN SOAL GERAK LURUS DI SMP - Aprianingsih, Dwi; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to find out the correlation between mathematical communication ability and the students ability to solve linear motion problem. The instrument  was an essay test which consists of 10 items. To measure mathematical communication ability amount to 5 items and to measure students’ ability to solve linear motion problem amount to 5 items. Intact group selected 32 students of SMP Negeri 1 Pontianak as research samples. Correlative analysis product moment and  significant coefficient correlation used  as data analysis techniques. The results of the analysis showed that  correlation score is 0,4917 and t hitung>ttabel= 3,0931>2,069. Based on the results of the analysis that there is a significant correlation between ability to mathematical communication and the ability to solve linear motion problem. Hoped that this research will be used as a benchmark by science teachers, to further improve students' mathematical communication ability in accordance with the purpose curriculum 2013. Keywords: Linear Motion, Mathematical Communication, Significance Test